Los voluntarios realistas de la ciudad de León (1823-1833) - Lorenzana Fernández, Antonio (Estudios humanísticos. Geografía, historia y arte, 1998)
The corps of "Voluntarios Realistas" was one fundamental pillar of the contrarevolution during the second absolutist restoration (1.823 - 1.833). Since the beginning a strong group of "Voluntarios" from Leon became the main support to the radical absolutism. They would be helped by the local clergymen and their bishop Joaquín Abarca. The "Voluntarios" came into riots several times with the Army, the Police, the conscriptions and even with the king Fernando VII, good example of these was the oustanding revolt in jannuary 1.833. The group was only not rnade by lower class subjects (crafmen and labourers) but also by some members of the local aristocracy and bourgeoise. The above mentioned revolt was lead by retired militaries and clergymen. After the rebellion failure the most notorions members took refuge in Portugal.